Copper mediated cyclization of 1-substituted enamides, dienamides and trienamides: regiochemistry, indigoid formation and methyl migration-aromatization. Issue 29 (20th July 2016) - Geden, Joanna V.; Clark, Andrew J.; Coles, Stuart R.; Guy, Collette S.; Ghelfi, Franco; Thom, Stephen
Graphical abstract: Highlights: Cu mediated reaction of 1-substituted enamides occurs via a radical-polar crossover. Termination can occur via elimination, addition of water or dimerization. Application of this approach to the indigoid skeleton may be possible. Methyl migration and aromatization can occur competitively for slow cyclizations. Abstract: Copper mediated cyclization of activated 1-substituted enamides occurs via a 5- endo radical-polar crossover process. Trichloroacetyl derivatives can undergo further reactions post cyclization (elimination of HCl or dimerization potentially via copper carbenoid intermediates). Reaction of α-halo trienamides derived from β-ionone furnish either β- or γ-lactams via 4- exo or 5- exo cyclizations respectively depending upon the enamide tautomer undergoing reaction. For the less reactive dichloroacetamide derivative a competing regioselective methyl migration-aromatization prior to cyclization is observed.